Impact of climate change on hydropower potential of the Lagdo dam, Benue River Basin, Northern Cameroon - R. M. Nonki (Copernicus Publications, 2021)
Nowadays, special attention is paid to hydroelectric production because it is an efficient, reliable, and renewable source of energy, especially in developing countries like Cameroon, where hydropower potential is the main source of electricity production. It also represents a useful tool to reduce the atmospheric greenhouse gas concentrations caused by human activities. However, it is the most sensitive industry to global warming, mainly because climate change will directly affect the quality, quantity of water resources (streamflow and runoff), which are the important drivers of hydropower potential. This study examined the response of hydropower potential to climate change on the Lagdo dam located in the Benue River Basin, Northern Cameroon. Hydropower potential was computed based on streamflow simulated using HBV-Light hydrological model with dynamically downscaled temperature and precipitation from the regional climate model REMO. These data were obtained using the boundary conditions of two general circulation models (GCMs): the Europe-wide Consortium Earth System Model (EC-Earth) and the Max Planck Institute-Earth System Model (MPI-ESM) under three Representative Concentrations Pathways (RCP2.6, RCP4.5 and RCP8.5). The results suggest that, the combination of decreased precipitation and streamflow, increased PET will negatively impact the hydropower potential in the Lagdo dam under climate change scenarios, models and future periods.